Can we prevent accidental injury to adolescents? A systematic review of the evidence. Issue 4 (December 1995) - Munro, J.; Coleman, P.; Nicholl, J.; Harper, R.; Kent, G.; Wild, D.
Abstract : OBJECTIVES: As part of the Department of Health strategy The Health of the Nation, a systematic review of published and unpublished literature relating to the effectiveness of interventions in reducing accidental injury in the population aged 15-24 years was carried out. METHODS: The literature was reviewed under the standard setting headings of road, work, home, and sports and leisure, and graded for quality of evidence and strength of recommendation using a scale published in the UK national epidemiologically based needs assessment programme. RESULTS: The most effective measures appear to be legislative and regulatory controls in road, sport, and workplace settings. Environmental engineering measures on the road and in sports have relatively low implementation costs and result in fewer injuries at all ages. There is little evidence that purely educational measures reduced injuries in the short term. Community based approaches may be effective in all age groups, and incentives to encourage safer behaviour hold promise but require further evaluation. The potential of multifactorial approaches seems greater than narrowly based linear approaches. CONCLUSIONS: Few interventions to reduce injury in adolescents have been rigorously evaluated using good quality randomised controlled trials, and where such evidence is available, fewer have been shown to be definitely worthwhile. Many studies relied on surrogate measures rather than actual injury rates, and substantial issues relating to the efficacy or implementation of preventive measures in adolescent and young adult populations remain unresolved.